Distillation troubleshooting - Kister, Henry Z. (AIChE : Wiley-Interscience, 2006)
THE FIRST BOOK OF ITS KIND ON DISTILLATION TECHNOLOGY. The last half-century of research on distillation has tremendously improved our understanding and design of industrial distillation equipment and systems. High-speed computers have taken over the design, control, and operation of towers. Invention and innovation in tower internals have greatly enhanced tower capacity and efficiency. With all these advances, one would expect the failure rate in distillation towers to be on the decline. In fact, the opposite is the case: the tower failure rate is on the rise and accelerating. Distillation Tr.
Keywords: Distillation apparatus -- Maintenance and repair.; elektronické knihy; electronic books